PENGARUH EFFLEURAGE MASSAGE TERHADAP TINGKAT NYERI DYSMENORRHEA PADA REMAJA PUTRI DI PANTI ASUHAN SMA ISLAM LIGA DAKWAH PADANG - Jufrika Gusni (Ensiklopedia of Journal, 2021)
Dysmenorrhea is a term for pain felt by women in the lower abdomen before or during menstruation. Data obtained from the Administration of the Padang Da'wah League Islamic High School Orphanage, there were 63 students from 3 classes in the Padang Da'wah League Islamic High School Orphanage. This study aims to find out how the Effect of Effleurage Massage on Dysmenorrhea Pain Levels in Young Women at the Islamic High School Orphanage LigaDakwah Padang in 2019. The design of the Quasy Experiment research was carried out at the Islamic High School LigaDakwah Padang Orphanage from March to September 2019. The population in the study this is 10 people. All of the population as samples were taken by accidental sampling. Processing computerized data through the univariate analysis stage, namely descriptive statistics in the form of mean, SD, and bivariate analysis using a dependent t-test with a 95% confidence stage. The results of the analysis showed that the average before the intervention was 5.3 and after the intervention was 3.3. Effleuraga massage actions. The results of the t-test obtained p-value = 0.000, then there is the effect of Effleurage Massage on the level of dysmenorrhea pain in adolescent girls. For the Principal of the Islamic High School Orphanage LigaDa'wah Padang, it is hoped that this will serve as material for consideration and input in providing education to take non-pharmacological actions to reduce the dysmenorrhea pain scale in adolescent girls and for institutions and to be able to develop independent actions to deal with dysmenorrhea pain.Keywords              : Teenager, Disminore, Effleurage Massage